Water Quality Modeling For Pollutant Carrying Capacity Assessment Using Qual2Kw In Bedog River - Akhmad Darajati Setiawan; M. Widyastuti; M. Pramono Hadi (Faculty of Geography, Universitas Gadjah Mada, 2018)
Considering the abundance of potential pollutant sources along Bedog River, i.e. highly dense residential areas, agricultural lands, and industrial areas, this study aimed to quantitatively assess the Pollutant Load (PL) and Pollutant Carrying Capacity (PCC) of the river based on Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD)parameters. The assessment employed a water quality modeling using Qual2Kw that provided not only the comprehensive values of PL and PCC but also the amount of PL that should be reduced to meet the PCC of every river segment. Water sampling and primary parameter measurement were conducted purposively in seven observation points, which included one point source and six non-point sources (river segments). River segments were determined according to the characteristics of land use and drainage system. Descriptive, graphic, and spatial analyses on water quality modeling show that the COD and BOD of Bedog River (2.24 km) indicates a small presence of PL compared to the river’s PCC. The PCC allows additional pollutant loads of 566.95 kg/day or 0.024 ton/hour BOD and 22,965.12 kg/day or 0.96 ton/hour COD. However, a high BOD in segments 3, 5, and 6 and a high COD in segment 5 imply the needs for PL reduction.